Managing cool‐season turfgrass without herbicides: Optimizing maintenance practices to control weeds. Issue 5 (23rd July 2020) - Hahn, Daniel; Sallenave, Rossana; Pornaro, Cristina; Leinauer, Bernd
Abstract: Bans on the use of synthetic herbicides require innovative management approaches to maintain the attractiveness and usability of turfgrass swards. Such measures should include the use of locally adapted cultivars that germinate and establish quickly, resulting in the densest possible stands. Additionally, a number of turfgrasses have been reported to produce allelopathic substances that inhibit common turfgrass weeds. Mowing heights should be set to achieve maximum weed suppression while still providing acceptable quality for desired use. Sustainable turfgrass management programs have led to a reduction in fertilizer inputs; however, without the availability of herbicides, fertilization regimes need to be re‐examined. The literature suggests that broadleaf weeds are reduced but never fully controlled when more N is applied; therefore, finding a balance between what is needed and what is environmentally safe and sustainable is critical. Organic herbicides include plant pathogens from the fungus Phoma and strains of the bacterium Pseudomonas fluorescens . Both can be used to control several weeds common to turfgrasses. Acetic acid has also been shown to have herbicidal activity; however, it has limited residual activity, and its efficacy remains questionable on mature weeds. Thermal weed control can be used to sterilize a seedbank or spot treat existing weeds. Future turfgrass breeding programs could focus on understanding and enhancing the allelopathic potential of turfgrasses to outcompete weeds more effectively. Furthermore, more research should be directed at assessing the competitiveness of certain turfgrasses against weeds within the limitations of producing turfgrass areas of acceptable aesthetics and playing quality.